ANALISIS FAKTOR YANG MEMPENGARUHI GENERASI MILENIAL DALAM PEMBELIAN KPR SYARIAH (BSI MALANG) - Muharram, Danu Purnama; Burhan, Muhammad Umar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research aims to identify factors that influence the millennial generation in purchasing Sharia Home Ownership Credit (KPR) at BSI Malang. In this research, the variables analyzed include income level, religiosity, price, and giving procedures. This research used a questionnaire with 190 millennial generation respondents, using logistic analysis with the help of STATA software which stated that income level, religiosity, and granting procedures were declared significant on the purchase of Sharia Home Ownership Credit (KPR), while the price variable had no significant effect on the purchase of Sharia KPR. In addition, this research can help banks design marketing and financing strategies for Sharia Home Ownership Credit (KPR) that are more effective in attracting the millennial generation as potential customers. Theoretically, this research contributes to the understanding of consumer behavior and purchasing decisions, especially in the context of purchasing Sharia mortgages by the millennial generation.